Concepções pedagógicas e práticas docentes em escolas da rede municipal de Aracaju/SE - Souza, Nielza da Silva Maia de (2010)
The main characteristic of this research is centered on a descriptive case study, which involves two public schools located in one of the peripheral districts at the southern part of Aracaju/Sergipe. This study is about conceptions of teaching practice, observed on school quotidian from the analysis of the elementary school teaching practice. The central research question is: what pedagogical conceptions base the everyday work of elementary school teachers of municipal schools in Aracaju? The specific objectives are: get a profile of the teachers who work at those schools; observe, interpret and analyze how these teachers develop their practice day by day. The theoretical basis are focused on pedagogical conceptions and teacher's knowledge provided by Becker (2005), Charlot (2005) and Freire (1996, 2005, 2007); teaching practices and school quotidian based on Heller (2008), Libâneo (2008) and Pimenta (1999, 2003), besides André (2002, 2005), Gil (1999), Laville and Dione (1999) who guided the methodological procedures of this study. The teachers and schools' anonymity are guaranteed. For that reason, they were renamed Schools "Sun ray" and "Moonlight" and the teachers were given flower's name,such as : Azalea , Dalea , Sunflower , Pansy , Lilly , Daisy , Orchid , Rose and Violet , and the research universe "Hopeville" district. The participants are composed by 30 teachers, except for 9 of them, who are non-intentional probabilistic sample. In the data collection were used the techniques of qualitative research with phenomenological approach (such as questionnaires, interviews, class observation and teachers' testimonials). The results found in the present study detect certain contradiction if compared to the discourse analyzed on official documents as well as in the speech of the staff involved in the investigation. Independently of being an old or new school, the results show markedly traditional practices in everyday school practices., since the lines while waiting for the beginning of the class through praying, snacks without break times, discipline control, desk in line etc. This dissertation is composed of six chapters: the first one introduces the topic; The second one deals with historical aspects and conceptual categories. The third one emphasizes the relationship to knowledge, teacher's knowledge and what happens inside school and pedagogical practices. The fourth chapter is specific to the research context when it comes to its universe and methodological path. The fifth one presents the results and data analysis, showing the teachers and their quotidian practices. The sixth chapter presents final considerations which deals with relevant aspects to the object study, intended to contributing to new studies on the area and possible interventions on the education of the municipal school area in Aracaju/Sergipe.